Femtosecond and Dual-Wavelength Picosecond Operations of Nd,La:SrF2 Disordered Crystal Laser - Zhipeng Qin; Zhen Qiao; Guoqiang Xie; Peng Yuan; Jingui Ma; Liejia Qian; Dapeng Jiang; Fengkai Ma; Fei Tang; Liangbi Su (IEEE Photonics Journal)
Both femtosecond and dual-wavelength picosecond operations of Nd,La:SrF2 disordered crystal laser have been demonstrated for the first time. In femtosecond operation, the laser generated mode-locked pulses with pulse duration of 156 fs, which is an average power of 90 mW, and a repetition rate of 108 MHz at the central wavelength of 1057 nm. In dual-wavelength picosecond operation, the laser generated synchronously mode-locked pulses with an average power of 500 mW and pulse duration of 9.9 ps. The mode-locked spectrum clearly shows two peaks at 1050.8 and 1059.0 nm, respectively. A periodic beat frequency of 2.2 THz is observed from the intensity autocorrelation trace, indicating the synchronous dual-wavelength mode-locking. Our experimental results show that Nd,La:SrF2 disordered crystal is an excellent laser material for femtosecond and dual-wavelength lasers near 1 μm wavelength.